A fully protected hydrogenase/polymer-based bioanode for high-performance hydrogen/glucose biofuel cells - Ruff, Adrian (2018)
Hydrogenases with Ni- and/or Fe-based active sites are highly active hydrogen oxidation catalysts with activities similar to those of noble metal catalysts. However, the activity is connected to a sensitivity towards high-potential deactivation and oxygen damage. Here we report a fully protected polymer multilayer/hydrogenase-based bioanode in which the sensitive hydrogen oxidation catalyst is protected from high-potential deactivation and from oxygen damage by using a polymer multilayer architecture. The active catalyst is embedded in a low-potential polymer (protection from high-potential deactivation) and covered with a polymer-supported bienzymatic oxygen removal system. In contrast to previously reported polymer-based protection systems, the proposed strategy fully decouples the hydrogenase reaction form the protection process. Incorporation of the bioanode into a hydrogen/glucose biofuel cell provides a benchmark open circuit voltage of 1.15 V and power densities of up to 530 µW cm−2 at 0.85 V.